Serum Extracellular Vesicle Stratifin Is a Biomarker of Perineural Invasion in Patients With Colorectal Cancer and Predicts Worse Prognosis - Hou, Wenyun; Pan, Meng; Xiao, Yi; Ge, Wei (Frontiers in Oncology, 2022)
Previous studies have shown that the presence of perineural invasion (PNI) is associated with a significantly worse prognosis in colorectal cancer (CRC) patients. In this study, we performed a detailed analysis of the diversity of extracellular vesicles (EV) between NPNI (non-PNI) and PNI using quantitative proteomics and aim to investigate the mechanisms underlying PNI in colorectal cancer. Quantitative proteomics technology was used to identify the proteome of serum-purified EVs from CRC patients with and without PNI (PNI and non-PNI (NPNI) groups, respectively) and healthy volunteers. Mass spectrometry data were verified by ELISA and Western blot analyses. The proteomic profile of serum EVs from the PNI group differed from that of those in the NPNI group. Serum-derived EVs from the PNI promoted more significant cellular mobility than EVs derived from the NPNI group. EV stratifin (SFN) expression levels demonstrated an area under the receiver operating characteristic curve values of 0.84 for discriminating patients with PNI from NPNI patients. Moreover, EV SFN expression levels were an independent predictor of CRC prognosis. In this study, we identified SFN as a potential biomarker for the diagnosis of PNI in stage II CRC patients.